EFFECTIVENESS OF ENDOSCOPIC SEPTOPLASTY IN DIFFERENT TYPES OF NASAL SEPTAL DEFORMITIES: OUR EXPERIENCE WITH NOSE EVALUATION - Nurmatovoa Aziza Kozimovna; Rustamov Azizbek Akbarovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In rhinologic practice, septal abnormalities are a common complaint and the most common cause of nasal obstruction. The use of the endoscope to treat septal abnormalities has grown in popularity since Lanza et al.'s 1991 initial presentation. This study aims to assess the efficacy of endoscopic septoplasty in correcting each of the seven categories of septal abnormalities identified by Mladina's classification. As far as we are aware, this is the first study to analyze objective results obtained before and after surgery, as well as subjective results obtained from the validated NOSE questionnaire, in order to assess the remedial ability of this procedure for each aberration. Even if endoscopic septoplasty is currently regarded as a dependable substitute for the traditional method, the optimal treatment option must be provided by correctly identifying the deformity prior to surgery.